The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1080/09638280500165120
|View full text |Cite
|
Sign up to set email alerts
|

The Disability Discrimination Act, a necessary, but not sufficient safeguard for people with progressive conditions in the workplace? The experiences of younger people with Parkinson's disease

Abstract: It can be very difficult for people with PD to continue in paid employment for more than a few years post diagnosis. The relatively low level of contact between people with PD who were in employment and health professionals suggest that employment retention is not seen as major role for this group of professionals. There is a need for positive action to support people with progressive conditions in the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 23 publications
4
65
1
1
Order By: Relevance
“…Our database switched to using the more sensitive Montreal Cognitive Assessment (MoCA) [e-supp ref 8] in 2009, but there were insufficient baseline MoCA data for analysis. Although 5e9% of PD patients in two surveys reported that impaired memory/concentration caused work-related disability [4,8], the role of cognition in LWF in PD has not been previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…Our database switched to using the more sensitive Montreal Cognitive Assessment (MoCA) [e-supp ref 8] in 2009, but there were insufficient baseline MoCA data for analysis. Although 5e9% of PD patients in two surveys reported that impaired memory/concentration caused work-related disability [4,8], the role of cognition in LWF in PD has not been previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…Inevitably, PD restricts PwP in participating in meaningful activities related to work, leisure or community and social life [33][34][35][36][37]. Many activities require too much time and effort, cause embarrassment, or are considered too dangerous by those close to them [38].…”
Section: Restrictions In Participationmentioning
confidence: 99%
“…Support and understanding of colleagues and the supervisor is crucial according to workers themselves [7,13,14,15,16]. A negative self-image, feelings of hopelessness related to employability and inability to set limits were mentioned by workers with musculoskeletal pain [17].…”
Section: Introductionmentioning
confidence: 99%